The role of renal dipeptidyl peptidase-4 in kidney disease: renal effects of dipeptidyl peptidase-4 inhibitors with a focus on linagliptin - Kanasaki, Keizo (Clin Sci (Lond), 2018)
Emerging evidence suggests that dipeptidyl peptidase-4 (DPP-4) inhibitors used to treat type 2 diabetes may have nephroprotective effects beyond the reduced renal risk conferred by glycemic control. DPP-4 is a ubiquitous protein with exopeptidase activity that exists in cell membrane-bound and soluble forms. The kidneys contain the highest levels of DPP-4, which is increased in diabetic nephropathy. DPP-4 inhibitors are a chemically heterogeneous class of drugs with important pharmacological differences. Of the globally marketed DPP-4 inhibitors, linagliptin is of particular interest for diabetic nephropathy as it is the only compound that is not predominantly excreted in the urine. Linagliptin is also the most potent DPP-4 inhibitor, has the highest affinity for this protein, and has the largest volume of distribution; these properties allow linagliptin to penetrate kidney tissue and tightly bind resident DPP-4. In animal models of kidney disease, linagliptin elicited multiple renoprotective effects, including reducing albuminuria, glomerulosclerosis, and tubulointerstitial fibrosis, independent of changes in glucagon-like peptide-1 (GLP-1) and glucose levels. At the molecular level, linagliptin prevented the pro-fibrotic endothelial-to-mesenchymal transition by disrupting the interaction between membrane-bound DPP-4 and integrin β1 that enhances signaling by transforming growth factor-β1 and vascular endothelial growth factor receptor-1. Linagliptin also increased stromal cell derived factor-1 levels, ameliorated endothelial dysfunction, and displayed unique antioxidant effects. Although the nephroprotective effects of linagliptin are yet to be translated to the clinical setting, the ongoing Cardiovascular and Renal Microvascular Outcome Study with Linagliptin in Patients with Type 2 Diabetes Mellitus (CARMELINA®) study will definitively assess the renal effects of this DPP-4 inhibitor. CARMELINA® is the only clinical trial of a DPP-4 inhibitor powered to evaluate kidney outcomes.